Gasteroid mycobiota of Rio Grande do Sul State, Brazil: Lysuraceae (Basidiomycota) - doi: 10.4025/actascibiolsci.v33i1.6726 - Vagner Gularte Cortez; Iuri Goulart Baseia; Rosa Mara Borges da Silva (Acta Scientiarum. Biological Sciences, 2011)
As part of a review of gasteroid mycobiota from Rio Grande do Sul State, in southern Brazil, members of the Lysuraceae (Phallales) family were studied. Fresh and herbarium specimens were analyzed macro- and micromorphologically. Lysurus cruciatus, L. cruciatus var. nanus (new record from Brazil) and L. periphragmoides have been collected in the area. Their specific limits, distribution and ecological data are discussed. Macroscopic photographs and line drawings of the basidiospores are presented.